2007
DOI: 10.2337/dc06-2011
|View full text |Cite
|
Sign up to set email alerts
|

Type 2 Diabetes and the Risk of Parkinson's Disease

Abstract: OBJECTIVE -To evaluate whether type 2 diabetes at baseline is a risk factor for Parkinson's disease.RESEARCH DESIGN AND METHODS -We prospectively followed 51,552 Finnish men and women 25-74 years of age without a history of Parkinson's disease at baseline. History of diabetes and other study parameters were determined at baseline using standardized measurements. Ascertainment of the Parkinson's disease status was based on the nationwide Social Insurance Institution's drug register data. Hazard ratios of incide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
281
4
3

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 404 publications
(296 citation statements)
references
References 38 publications
8
281
4
3
Order By: Relevance
“…A hospital-based case-control study [540] Several recent prospective studies examined the relation between diabetes and PD. Based on residents in five geographic areas in Finland, one large study reported higher risk of PD associated with diabetes assessed through a combination of self-report, hospital discharge information and prescription data (HR 1.85, 95% CI 1.22-2.79) [632]. Similarly, the Physicians Health Study observed increased risk of PD associated with self-reported diabetes (RR 1.34, 95% CI 1.01-1.77) [633].The association between diabetes and PD was modified by BMI (p for interaction 0.04); PD risk was decreased among individuals with both diabetes and high BMI.…”
Section: Diabetesmentioning
confidence: 99%
See 1 more Smart Citation
“…A hospital-based case-control study [540] Several recent prospective studies examined the relation between diabetes and PD. Based on residents in five geographic areas in Finland, one large study reported higher risk of PD associated with diabetes assessed through a combination of self-report, hospital discharge information and prescription data (HR 1.85, 95% CI 1.22-2.79) [632]. Similarly, the Physicians Health Study observed increased risk of PD associated with self-reported diabetes (RR 1.34, 95% CI 1.01-1.77) [633].The association between diabetes and PD was modified by BMI (p for interaction 0.04); PD risk was decreased among individuals with both diabetes and high BMI.…”
Section: Diabetesmentioning
confidence: 99%
“…Two large prospective studies reported increased PD risk associated with diabetes [632,633], one prospective study reported no association [634], whereas another reported lower risk of diabetes among PD cases [635]. Surveillance bias may cause a spurious positive association, an issue that may be of particular importance for a disease such as diabetes that can remain undetected during a long period of time.…”
Section: Diabetesmentioning
confidence: 99%
“…In aging, hyperglycemia is also associated with PD through damage to the central nervous system, a consequence of long-term exposure to glucose (Tomlinson and Gardiner 2008;Hu et al 2007). Epidemiologic studies suggest that previous type 2 diabetes is also a risk factor for developing PD (Mercer et al 2005).…”
Section: Brain Neurons and Parkinson's Diseasementioning
confidence: 99%
“…This is exemplified by renal nephropathy, myocardial disease, stroke, Alzheimer's and Parkinson's disease (Almdal et al, 2004;Biessels et al, 2006;Burdo et al, 2009;Hallows et al, 2010;Hu et al, 2007;Maher & Schubert, 2009;Schernhammer et al, 2011). Several drugs are currently used in the clinical setting to activate AMPK in patients suffering from type 2 diabetes or obesity.…”
Section: How Does the Compartment-specific Action Of Ampk Impact Cellmentioning
confidence: 99%